A series of patients with hospital-acquired diabetic ketoacidosis (HADKA): a descriptive analysis. Issue 6 (2022) - Williams, David M; Taverner, Sofia; Watson, Rebecca; George, Siba; Edwards, Amanda; Shaikh, Ayesha; Udiawar, Maneesh
No abstract available